Analysis of The Effectiveness of Fiscal Policy in Driving the Regional Economy: Case Study in South Sulawesi Province, Indonesia - S, Masnawaty; Sahade, Sahade; Rijal, Syamsu (IJBLE Scientific Publications Community Inc., 2023)
This research investigates the relationship between fiscal policy, as implemented by the Indonesian government, and the economic growth of the South Sulawesi province. The economic landscape in Sulawesi is characterized by small-scale activities, primarily centered around resource extraction, agriculture, and fishing. The study aims to analyze the impact of fiscal policies on regional economic development in South Sulawesi, focusing on government budget allocation, infrastructure spending, social welfare programs, and tax policies. The research employs a quantitative approach, utilizing regression analysis to examine the causal relationships between fiscal policy variables and regional economic indicators. The results indicate a significant influence of fiscal policy and its effectiveness on the regional economy, emphasizing the importance of tailored fiscal strategies for sustainable economic growth. The findings offer valuable insights for policymakers at both regional and national levels to formulate effective economic policies aligned with the specific needs of the South Sulawesi province. Moreover, the study contributes to the broader literature on fiscal policy effectiveness, particularly within the context of regional economies.